Assessment of safety culture for occupational radiation protection in medical practices : a case study of Parirenyatwa Group of Hospitals, Harare, Zimbabwe - Chipuru, Justice (Midlands State University, 2020)
Although highly beneficial, the use of ionizing radiation and nuclear technologies poses risks to workers, the public and the environment. The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) reported that medical occupational exposure contributes 75% of the 9.6 million workers exposed to artificial sources of radiation (UNSCEAR; 2016). This is attributed to the widespread medical applications of the technologies that include dental radiology; diagnostic radiology (general X-ray, Computed Tomography, Mammography, bone densitometry); Interventional radiology (fluoroscopy, angiography); Radiotherapy and Nuclear Medicine (diagnosis and treatment). The exposure emanates from practices and interventions, where the former involves normal operations while interventions seek to reduce the existing radiation exposure, in emergency situations (IAEA, 2015).